Preface
This is a solution manual for Tom Apostol’s Introduction to Analytic Number Theory. Since graduating, I decided to work out all solutions to keep my mind sharp and act as a refresher. There are many problems in this book that are challenging and worth doing on your own, so I recommend referring to this manual as a last resort. The most up to date manual can be found at gregoryhurst.com. Please report any errors you may ﬁnd.
Clearly some problems are harder than others so I used the following markers to indicate exercises I found hard:
(+) denotes problems I found particularly challenging. (++) denotes what I considered to be the most challenging problem of the chapter.
Furthermore I kept track of the exercises from which I learned the most, which are naturally the ones I recommend the most:
Exercise 1.24 
Exercise 1.30 
Exercise 2.8 
Exercise 3.12 
Exercise 4.24 
Exercise 4.25 
Exercise 4.26 
Exercise 4.27 
Exercise 4.28 
Exercise 4.29 
Exercise 4.30 
Exercise 5.13 
Exercise 5.18 
Exercise 5.19 
Exercise 5.20 
Exercise 6.18 
Exercise 10.8 
Exercise 10.9 
Exercise 10.13 
Exercise 11.15 
Exercise 11.16 
Exercise 12.12 
Exercise 12.19 
Exercise 13.10 
Exercise 14.5 
ii
Contents
Preface 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
ii 

1 The Fundamental Theorem of Arithmetic 
1 

2 Arithmetical Functions and Dirichlet Multiplication 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
11 

3 Averages of Arithmetical Functions 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
32 

4 Some Elementary Theorems on the Distribution of Prime Numbers 
51 

5 Congruences 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
73 

6 Finite Abelian Groups and Their Characters 
84 

7 Dirichlet’s Theorem on Primes in Arithmetic Progressions 
92 

8 Periodic Arithmetic Functions and Gauss Sums 
96 

9 Quadratic Residues and the Quadratic Reciprocity Law 
107 

10 Primitive Roots 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
116 

11 Dirichlet Series and Euler Products 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
126 

12 The Functions ζ(s) and L(s, χ) 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
141 

13 Analytic Proof of the Prime Number Theorem 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
160 

14 Partitions 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
170 

End 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
. 
185 
iii 
Chapter 1 The Fundamental Theorem of Arithmetic
In there exercises lower case latin letters a, b, c,
Prove each of the statements in Exercises 1 through 6.
Exercise 1.1. If (a, b) = 1 and if c  a and d  b, then (c, d) = 1.
Proof. Since a and b are relatively prime, there are integers x and y such that ax + by = 1.
Also because c  a and d  b, we have a = cn and b = dm for some integers n and m. c(nx) + d(my) = 1, which implies (c, d) = 1.
Exercise 1.2. If (a, b) = (a, c) = 1, then (a, bc) = 1.
Proof. Since a is relatively prime to both b and c, there are integers x _{1} , x _{2} , y _{1} , y _{2} such that
, x, y, z represent integers.
Thus
ax _{1} + by _{1} = 1
and
ax _{2} + cy _{2} = 1.
Multiplying gives
(ax _{1} + by _{1} )(ax _{2} + cy _{2} ) = 1 
=⇒ 
a ^{2} x _{1} x _{2} + acx _{1} y _{2} + 
abx _{2} y _{1} + bcy _{1} y _{2} = 1 
=⇒ 
a(ax _{1} x _{2} + cx _{1} y _{2} + 
bx _{2} y _{1} ) + (bc)(y _{1} y _{2} ) = 1 

=⇒ 
(a, bc) = 1. 
Exercise 1.3. If (a, b) = 1, then (a ^{n} , b ^{k} ) = 1 for all n ≥ 1, k ≥ 1.
Proof.
Suppose p  a ^{n} and p  b ^{k} for some prime p.
Then p  a and p  b, as p is prime.
This
implies p  (a, b), a contradiction. 


Exercise 1.4. If (a, b) = 1, then (a + b, a − b) is either 1 or 2. 

Proof. Since (a, b) = 1, there are integers x and y such that ax + by = 1. Then 

(a + b)(x + y) + (a − b)(x − y) = 
(ax + bx + ay + by) + (ax − bx − ay + by) 

= 2ax + 2by = 2. 

Thus (a + b, a − b) ≤ 2, i.e. (a + b, a − b) is either 1 or 2. 

1
2
Chapter 1 Solutions
Exercise 1.5.
If (a, b) = 1, then (a + b, a ^{2} − ab + b ^{2} ) is either 1 or 3.
Proof. Let g = (a + b, a ^{2} − ab + b ^{2} ). Since (a + b) ^{2} −(a ^{2} − ab + b ^{2} ) = 3ab, we have g  3ab. This means each prime factor p of g must divide 3, a, or b. However without loss of generality , if p  a then p  (a + b) − a = b. This contradicts (a, b) = 1, and so p ab. Therefore (g, ab) = 1,
which means g  3, i.e.
g = 1 or g = 3.
Exercise 1.6.
If (a, b) = 1 and if d  a + b, then (a, d) = (b, d) = 1.
Proof.
for some integer n, and so g  b. shows (b, d) = 1.
Let g = (a, d), which means g  a and g  d. Additionally, d  a + b implies b = nd − a
Thus g  (a, b), which forces g = 1. The same argument
Exercise 1.7. A rational number a/b with (a, b) = 1 is called a reduced fraction. If the sum of two reduced fractions in an integer, say (a/b) + (c/d) = n, prove that b = d.
Proof. Since n = (ad + bc)/(bd), both b and d divide ad + bc. This means b  ad and d  bc,
but since (a, b) = (c, d) = 1 we must have b  d and d  b.
Therefore b = d.
Exercise 1.8. An integer is called squarefree if it is not divisible by the square of any prime. Prove that for every n ≥ 1 there exist uniquely determined a > 0 and b > 0 such that n = a ^{2} b, where b is squarefree.
Proof. Suppose n ≥ 1 and n = p ^{α} ^{1} ··· p ^{α} ^{k} . Deﬁne
1
k
a = p
α _{1} /2
1
··· p
α _{k} /2
k
and
b = p ^{α} ^{1}
1
^{m}^{o}^{d} ^{2}
_{·}_{·}_{·} _{p} α _{k} mod 2 k
^{.}
We then have n = a ^{2} b since α _{i} = 2 α _{i} /2 + (α _{i} mod 2). Moreover, b is square free.
c ^{2} d. This
forces a = c as they are both positive. Substituting a = c into a ^{2} b = c ^{2} d shows b = d. Hence
>
However, d is squarefree so it follows that a ^{2}  c ^{2} . Similarly c ^{2}  a ^{2} , thus a ^{2}  = c ^{2} .
Now suppose n =
c ^{2} d for
c
>
0 and
d
0.
Then a ^{2} b = c ^{2} d which means a ^{2}

this decomposition is unique.
Exercise 1.9. For each of the following statements, either give a proof or exhibit a counter example.
(a) 
If b ^{2}  n and a ^{2}  n and a ^{2} ≤ b ^{2} , then a  b. 

(b) 
If b ^{2} is the largest square divisor of n, then a ^{2}  n implies a  b. 

Solution. 

(a) 
False: 
Let n = 36, a = 2, and b = 3. 
(b)
If n = p ^{α} ^{1} ··· p ^{α} ^{k}
1
k
and b ^{2} is the largest square divisor of n, then by Exercise 1.8,
b = p
α _{1} /2
1
··· p
α _{k} /2 k
^{.}
If a ^{2}  n, then a = p ^{β} ^{1} ··· p ^{β} ^{k} , where β _{i} ≤ α _{i} /2 .
1
k
Thus a  b.
Exercise 1.10. Given x and y, let m = ax + by, n = cx + dy, where ad − bc = ±1. Prove that (m, n) = (x, y).
3
Proof. Observe m and n are expressed as linear combinations of x and y. This means (x, y)  m and (x, y)  n, which implies (x, y)  (m, n). Treating m = ax + by and n = cx + dy as a system of linear equations, solving gives
_{x} _{=} dm − bn ad − bc
and
y = ^{a}^{n} ^{−} ^{c}^{m} ad − bc ^{.}
Furthermore, since ad − bc = ±1, then x = ±(dm − bn) and y = ±(an − cm). So applying the exact argument from above, we conclude (m, n)  (x, y). This can only happen when
(x, y) = (m, n), and since gcd’s are positive, (x, y) = (m, n). 

Exercise 1.11. Prove that n ^{4} + 4 is composite if n > 1. 

Proof. Factoring shows 

n ^{4} + 4 = (n ^{4} + 4n ^{2} + 4) − 4n ^{2} 

= (n ^{2} + 2) ^{2} − (2n) ^{2} 

= (n ^{2} + 2n + 2)(n ^{2} − 2n + 2). 

Observe for n > 1, both factors are larger than 1 and so n ^{4} + 4 is composite. 

In Exercises 12, 13, and 14, a, b, c, m, n denote positive integers.
Exercise 1.12. For each of the following statements, either give a proof or exhibit a counter example.
(a) 
If a ^{n}  b ^{n} then a  b. 
(b) 
If n ^{n}  m ^{m} then n  m. 
(c) 
If a ^{n}  2b ^{n} and n > 1, then a  b. 
Solution.
(a) True: Suppose a = p ^{α} ^{1} ··· p ^{α} ^{k} . Then a ^{n}  b ^{n} implies b ^{n} = p ^{n}^{α} ^{1} ··· p ^{n}^{α} ^{k} · q ^{n}^{β} ^{1} ··· q
means b = p ^{α} ^{1} ··· p ^{α} ^{k} · q ^{β} ^{1} ··· q
1
1
k
β
l
1
k
1
l
, i.e.
a  b.
1
k
nβ _{l}
l
. This
(b) 
False: 
Let n = 8 and m = 12. 
(c) 
True: 
If a is odd then (a, 2) = 1 and a ^{n}  b ^{n} , hence (a) implies a  b. 
Now suppose a = 2 ^{s} d where s > 0 and d is odd.
Since a ^{n}  2b ^{n} ,
2b ^{n} = 2 ^{n}^{s} d ^{n} m
for some integer m. Thus
_{b} n _{=} _{2} n(s−1)+(n−1) _{d} n _{m}_{.}
Since n − 1 > 0, 2 ^{n}^{(}^{s}^{−}^{1}^{)}^{+}^{(}^{n}^{−}^{1}^{)} is not an nth power, which means m must be even. Therefore
b ^{n} = 2 ^{n}^{s} d ^{n} (m ^{} ) ^{n} = a ^{n} (m ^{} ) ^{n} ,
and so a  b.
Exercise 1.13. If (a, b) = 1 and (a/b) ^{m} = n, prove that b = 1. If n is not the mth power of a positive integer, prove that n ^{1}^{/}^{m} is irrational.
4
Chapter 1 Solutions
Proof.
If (a/b) ^{m} = n, then a ^{m} /b ^{m} − n/1 = 0.
Thus by Exercise 1.7, b ^{m}  = 1, and so b = 1.
Next suppose n ^{1}^{/}^{m} = a/b where (a, b) = 1. Then n = (a/b) ^{m} , which we now know implies
b = 1. Therefore n = a ^{m} , i.e. n is an mth power.
Exercise 1.14.
[Hint : Consider d = (a, c).]
If (a, b) = 1 and ab = c ^{n} , prove that a = x ^{n} and b = y ^{n} for some x and y.
Proof. Suppose a = p ^{a} ^{1} ··· p ^{a} ^{k}
1
_{k}
and so
and b = q
b
1
1
··· q
b
l
l
where all p _{i} and q _{j} are distinct. Then
c ^{n} = p ^{a} ^{1} ··· p ^{a} ^{k} · q
1
k
b
1
1
··· q
b
l
l
^{,}
c = p ^{a} ^{1} ^{/}^{n} ··· p ^{a} ^{k} ^{/}^{n} · q
1
k
b _{1} /n
1
··· q
b _{l} /n l
^{.}
Since each p _{i} and q _{j} are distinct, n  a _{i} and n  b _{j} . Therefore a and b are nth powers.
Exercise 1.15. Prove that every n ≥ 12 is the sum of two composite numbers.
Proof.
odd, then n = 9 + (n − 9) and n − 9 > 2 is even.
If n is even, then n = 4 + (n − 4) and n − 4 > 2 is even.
On the other hand, if n is
Exercise 1.16. Prove that if 2 ^{n} − 1 is prime, then n is prime.
Proof. Suppose n is composite and n = ab for some a > 1 and b > 1. Then
2 ^{n} − 1 = (2 ^{a} ) ^{b} − 1 = (2 ^{a} − 1)(2 ^{a}^{(}^{b}^{−}^{1}^{)} + 2 ^{a}^{(}^{b}^{−}^{2}^{)} + ··· + 2 ^{a} + 1).
Since both factors are greater than one, 2 ^{n} − 1 must be composite.
Exercise 1.17. Prove that if 2 ^{n} + 1 is prime, then n is a power of 2.
Proof. Suppose n = 2 ^{s} d where d is odd and d > 1. Then
_{2} _{n} _{+} _{1} _{=} _{(}_{2} _{2} s _{)} _{d} _{+} _{1} _{=} _{(}_{2} _{2} s
Furthermore since d > 1 is odd,
_{+} _{1}_{)}_{(}_{2} 2 s (d−1) _{−} _{2} 2 s (d−2) _{+} _{·}_{·}_{·} _{+} _{2} 2 s ·2 _{−} _{2} 2 s _{+} _{1}_{)}_{.}
(2 ^{2} ^{s} ^{(}^{d}^{−}^{1}^{)} − 2 ^{2} ^{s} ^{(}^{d}^{−}^{2}^{)} ) + · · · + (2 ^{2} ^{s} ^{·}^{2} − 2 ^{2} ^{s} ) + 1 > 0 + ··· + 0 + 1 = 1.
Hence both factors are larger than 1 and so 2 ^{n} + 1 is composite. Thus if 2 ^{n} + 1 is prime,
then d = 1, i.e.
n is a power of 2.
Exercise 1.18. If m
= n compute the gcd (a ^{2} ^{m} + 1, a ^{2} ^{n} + 1) in terms of a.
[Hint : Let
A _{n} = a ^{2} ^{n} + 1 and show that A _{n}  (A _{m} − 2) if m > n.]
5
Solution. Let g = (A _{m} , A _{n} ), where m > n and deﬁne A _{k} = a ^{2} ^{k} + 1. Now
A _{m} − 2 = a ^{2} ^{m} − 1
= (a ^{2} ^{n} ) ^{2} ^{m}^{−}^{n} − 1
= (a ^{2} ^{n} + 1)(a ^{2} ^{n} ^{(}^{2} ^{m}^{−}^{n} ^{−}^{1}^{)} − a ^{2} ^{n} ^{(}^{2} ^{m}^{−}^{n} ^{−}^{2}^{)} + ··· + a ^{2} ^{n} − 1)
= A _{n} · (a ^{2} ^{n} ^{(}^{2} ^{m}^{−}^{n} ^{−}^{1}^{)} − a ^{2} ^{n} ^{(}^{2} ^{m}^{−}^{n} ^{−}^{2}^{)} + ··· + a ^{2} ^{n} − 1),
and hence A _{n}  (A _{m} − 2).
is even, then A _{k} is odd and hence g = 1. giving g = 2.
Exercise 1.19.
with a _{1}
sion formula a _{n}_{+}_{1}
This shows g  A _{m} − 2 and g  A _{m} , thus by linearity g  2.
If a
On the other hand, if a is odd, then A _{k} is even,
The Fibonacci sequence 1, 1, 2, 3, 5, 8, 13, 21, 34,
=
a _{n} + a _{n}_{−}_{1} ,
= a _{2}
=
1.
is deﬁned by the recur
1 for each
Prove that (a _{n} , a _{n}_{+}_{1} ) =
n. 

Proof. 
Induct on n. It’s clear (a _{1} , a _{2} ) = 1. Let n > 1 and assume (a _{n}_{−}_{1} , a _{n} ) = 1. Then 
(a _{n} , a _{n}_{+}_{1} ) = (a _{n} , a _{n} + a _{n}_{−}_{1} ) = (a _{n} , a _{n}_{−}_{1} ) = 1.
Exercise 1.20. Let d = (826, 1890). Use the Euclidean algorithm to compute d, then express d as a linear combination of 826 and 1890.
Solution. Applying the Euclidean algorithm,
1890 = 2 · 826 + 238
826 
= 
3 · 238 + 112 
238 
= 
2 · 112 + 14 
112 
= 8 · 14 + 0, 
hence d = 14. Through back substitution,
14 = 
238 − 2 · 112 
= 
(1890 − 2 · 826) − 2(826 − 3 · 238) 
= 
(1890 − 2 · 826) − 2(826 − 3 · (1890 − 2 · 826)) 
= 
7 · 1890 − 16 · 826. 
Exercise 1.21. The least common multiple (lcm) of two integers a and b is denoted by [a, b] or by aM b, and is deﬁned as follows.
[a, b] = ab/(a, b)
[a, b] = 0
if a
= 0 and b
= 0
if a = 0 or b = 0.
Prove that the lcm has the following properties:
(a) If a = ^{}
(b)
(c)
(D and M are distributive with respect to each other.)
∞
a
i
and b = ^{}
b
i=1 ^{p} i
∞
i=1 ^{p} i
i
then [a, b] = ^{}
∞
i=1 ^{p} i
c
(aDb)Mc = (aMc)D(bMc).
(aM b)Dc = (aDc)M (bDc).
i
, where c _{i} = max{a _{i} , b _{i} }.
6
Chapter 1 Solutions
Proof.
(a) If c _{i} = max{a _{i} , b _{i} } and m _{i} = min{a _{i} , b _{i} }, then by deﬁnition [a, b] = ^{}
it’s easy to see a _{i} + b _{i} = c _{i} + m _{i} , and hence [a, b] = ^{}
∞
i=1 ^{p}
c
i
i
^{.}
∞ a _{i} +b _{i} −m _{i} i=1 ^{p} i
For the next parts assume a = ^{}
∞
i=1 ^{p} i
a
i
, b = ^{}
∞
b
i=1 ^{p} i
i
, and c = ^{}
∞
i=1 ^{p}
c
i
i
^{.}
(b) 
We have 
and 
[(a, b), c] = ^{} p
min{a _{i} ,b _{i} }
i
, ^{} p
c
i
i
= ^{} p
max{min{a _{i} ,b _{i} },c _{i} }
i
([a, c], [b, c]) = ^{} p
max{a _{i} ,c _{i} }
i
, ^{} p
max{b _{i} ,c _{i} }
i
= ^{} p
min{max{a _{i} ,c _{i} },max{b _{i} ,c _{i} }} i
^{.}
. Now
To show these exponents are equal, we will compare the two in a table.
ordering 
max{min{a _{i} , b _{i} }, c _{i} } 
min{max{a _{i} , c _{i} }, max{b _{i} , c _{i} }} 

a _{i} ≥ b _{i} ≥ c _{i} 
b 
i 
b 
i 
a _{i} ≥ c _{i} ≥ b _{i} 
b 
i 
b 
i 
b _{i} ≥ a _{i} ≥ c _{i} 
b 
i 
b 
i 
b _{i} ≥ c _{i} ≥ a _{i} 
a 
i 
a 
i 
c _{i} ≥ a _{i} ≥ b _{i} 
b 
i 
b 
i 
c _{i} ≥ b _{i} ≥ a _{i} 
a 
i 
a 
i 
This shows max{min{a _{i} , b _{i} }, c _{i} } = min{max{a _{i} , c _{i} }, max{b _{i} , c _{i} }} and the result follows.
(c) We have
and
([a, b], c) = ^{} p
max{a _{i} ,b _{i} }
i
, ^{} p
c
i
i
= ^{} p
min{max{a _{i} ,b _{i} },c _{i} }
i
[(a, c), (b, c)] = ^{} p
min{a _{i} ,c _{i} }
i
, ^{} p
min{b _{i} ,c _{i} }
i
= ^{} p
max{min{a _{i} ,c _{i} },min{b _{i} ,c _{i} }}
i
^{.}
To show these exponents are equal, we will compare the two in a table.
ordering 
min{max{a _{i} , b _{i} }, c _{i} } 
max{min{a _{i} , c _{i} }, min{b _{i} , c _{i} }} 

a _{i} ≥ b _{i} ≥ c _{i} 
c 
i 
c 
i 
a _{i} ≥ c _{i} ≥ b _{i} 
b 
i 
b 
i 
b _{i} ≥ a _{i} ≥ c _{i} 
c 
i 
c 
i 
b _{i} ≥ c _{i} ≥ a _{i} 
b 
i 
b 
i 
c _{i} ≥ a _{i} ≥ b _{i} 
b 
i 
b 
i 
c _{i} ≥ b _{i} ≥ a _{i} 
b 
i 
b 
i 
This shows min{max{a _{i} , b _{i} }, c _{i} } = max{min{a _{i} , c _{i} }, min{b _{i} , c _{i} }} and the result follows.
Exercise 1.22. Prove that (a, b) = (a + b, [a, b]).
Lemma 1.22. If (c, d) = 1, then (c + d, cd) = 1.
Proof of Lemma.
generality p  c, and so p  (c + d) − c = d. This means p  (c, d), a contradiction.
Suppose p 
c + d
and p

cd for some prime p.
Then without loss of
7
Proof of Exercise. Note by Theorem 1.4 (c) if c > 0, then (ac, bc) = c(a, b). Now if g = (a, b), then a = gn and b = gm for some integers n and m. By Lemma 1.22,
(a + b, [a, b]) = (a + b, ab/g)
= (g(n + m), ±gnm)
= g(n + m, nm)
= g.
Exercise 1.23. The sum of two positive integers is 5264 and their least common multiple is 200 340. Determine the two integers.
Solution. We have a + b = 5264 and [a, b] = 200 340. So by Exercise 1.22,
200 340 = ab/(5264, 200 340) = ab/28,
and therefore
a + b = 5264
and
ab = 5 609 520.
Assuming a < b, solving the system gives a = 1484 and b = 3780.
Exercise 1.24.(++) Prove the following multiplicative property of the gcd:
(ah, bk) = (a, b)(h, k)
a
(a, b) ^{,}
(h, k) (a, b) ^{,}
k
b
(h, k) ^{.}
h
In particular this shows that (ah, bk) = (a, k)(b, h) whenever (a, b) = (h, k) = 1.
Lemma 1.24. If n, m, and g > 0 are integers, then g = (n, m) if and only if (n/g, m/g) = 1.
Proof of Lemma. By Theorem 1.4 (c),
(n, m) = g ⇐⇒ (g(n/g), g(m/g)) = g ⇐⇒ g(n/g, m/g) = g ⇐⇒ (n/g, m/g) = 1.
Proof of Exercise. Let a _{1} = a/(a, b), b _{1} = b/(a, b), h _{1} = h/(h, k), k _{1} = k/(h, k). Then apply ing Lemma 1.24,
Now deﬁne α =
(ah, bk) = (a, b)(h, k)
a
(a, b) ^{,}
(h, k) (a, b) ^{,}
k
b
(h, k)
h
⇐⇒ (a _{1} h _{1} , b _{1} k _{1} ) = (a _{1} , k _{1} )(b _{1} , h _{1} )
⇐⇒
a
1
h
1
(a _{1} , k _{1} ) (b _{1} , h _{1} ) ^{,}
b
1
k
_{k} 1 _{)} = 1.
1
(b _{1} , h _{1} ) (a _{1} ,
,k _{1} ) ^{,} ^{γ} ^{=}
(a
_{1}
a
1
h
,h _{1} ) ^{,} ^{β} ^{=}
1
(b
_{1}
b
,h _{1} ) ^{,} ^{δ} ^{=}
1
(b
_{1}
(α, δ) = 1
and
k
_{,}_{k} _{1} _{)} . Then by Lemma 1.24,
1
(a
_{1}
(γ, β) = 1.
8
Chapter 1 Solutions
Additionally, note
α =
a
d _{1} (a, b)
^{a}^{n}^{d}
^{β} ^{=}
b
d _{2} (a, b)
for some d _{1} and d _{2} , so Lemma 1.24 shows (α, β) = 1 and similarly (γ, δ) = 1. This means
αγ and βδ can share no positive divisors other than 1, that is (αγ, βδ) = 1.
Prove each of the following statements in Exercises 25 through 28. All integers are positive.
Exercise 1.25.
If (a, b) = 1 there exist x > 0 and y > 0 such that ax − by = 1.
Proof. If a = 1 then take x = b + 1 and y = 1, so we can assume a > 1 and b > 1. Since (a, b) = 1, there are x and y such that ax+by = 1. If x > 0 and y < 0, we’re done. Otherwise we make a few quick observations.
Molto più che documenti.
Scopri tutto ciò che Scribd ha da offrire, inclusi libri e audiolibri dei maggiori editori.
Annulla in qualsiasi momento.